The economics and ethics of human induced climate change - Spash, Clive L.; Gattringer, Clemens (Vienna, 2015)
"Human induced climate change poses a series of ethical challenges to the current political economy, although it has often be regarded by economists as only an ethical issue for those concerned about future generations. The central debate in economics has then concerned the rate at which future costs and benefits should be discounted. Indeed the full range of ethical aspects of climate change are rarely even discussed. Despite recent high profile and lengthy academic papers on the topic the ethical remains at best superficial within climate change economics. Recognising the necessary role of ethical judgment poses a problem for economists who conduct exercises in cost-benefit analysis and deductive climate modelling under the presumption of an objectivity that excludes values. Priority is frequently given to orthodox economic methodology, but that this entails a consequentialist utilitarian philosophy is forgotten while the terms of the debate and understanding is simultaneously restricted. We set out to raise the relevance of a broader range of ethical issues including: intergenerational ethics as the basis for the discount rate, interregional distribution of harm, equity and justice issues concerning the allocation of carbon budgets, incommensurability in the context of compensation, and the relationship of climate ethics to economic growth. We argue that the pervasiveness of strong uncertainty in climate science, incommensurability of values and non-utilitarian ethics are inherent features of the climate policy debate. That mainstream economics is ill-equipped to address these issues relegates it to the category of misplaced concreteness and its policy prescriptions are then highly misleading misrepresentations of what constitutes ethical action."